Spatiotemporal contingencies in tourists’ intradiurnal mobility patterns - Grinberger, A. Yair; Shoval, Noam (Journal of travel research, 2019)
Tourists’ activity patterns result from complex interactions between time-space constraints and cognitive, social, cultural, and emotional factors. Accordingly, tourists’ intradestination activity is studied today from multiple perspectives. Yet knowledge regarding the interrelationships between these factors is limited. The current research aims to contribute to the bridging of this gap, by studying tourists’ activity patterns and the time-space resource allocation decisions they reflect. Using a smartphone application, 384 tourists’ activity days in the cities of Tel-Aviv and Jerusalem were tracked and characterized in terms of resource allocation patterns, identifying three distinct behavioral patterns. The effects of various personal and external factors on group membership were then assessed. The results uncover complex relationships between various decision-making dimensions, where interdimensional interactions occur at multiple spatial scales and decision-making instances. These findings suggest that activity patterns emerge from a decision time-space in which effects are contingent upon each other across scales and behavioral dimensions.